The Birds, Our Teachers : Essays in Orni-Theology - Stott, John (Candle Books, 1999)
In this volume the author expands on Martin Luther's exhortation from the Sermon on the Mount "Let the little birds be your theologians". He reveals lessons on faith from the feeding of ravens, on repentance from the migration of storks, on freedom from the flight of the eagle
Include Color Illustration
Keywords: Christian life--Anglican authors -- Birds--Religious aspects--Christianity -- Bird watching